Immunotropic and Immunogenic Properties of Nonspecific Yersinia Porins - O. D. Novikova; O. Yu. Portnyagina; O. P. Vostrikova; V. A. Ivanis (Вестник войск РХБ защиты, 2023)
The purpose of the study is to summarize our own data and literature data on the significance of poreforming proteins of the outer membrane of Yersinia as factors of their pathogenicity and as diagnostic and protective antigens, and their role in pathological processes considered non-infectious. In the last decades of the last century, the epidemic significance of intestinal yersiniosis caused by the bacteria of Yersinia genus, Yersinia pseudotuberculosis and Yersinia enterocolitica, which are the «doubles» of the plague pathogen (Yersinia pestis) by genetic, cultural, biochemical, and other properties, has significantly increased. It has been established that acute yersiniosis infections without effective treatment can pass into secondary focal forms, leading to the development of systemic diseases that were not previously considered infectious (for example, Grave’s disease). They are characterized by multiple organ lesions, dysfunctions of the cardiovascular and nervous systems, musculoskeletal system, urinary system and gastrointestinal tract, which is a consequence of autoimmune processes based on the ability of Yersinia to molecular mimicry. The paper shows that porins play a significant role in the development of the infectious process and can be considered as pathogenic factors of bacteria. Together with other components of the outer membrane of gram negative bacteria, they provide adhesion, invasion and colonization of the cells of the host organism by bacteria. Porins can affect a number of eukaryotic cell functions, including cytokine expression, receptor activation, apoptosis induction, and regulation of the actin cytoskeleton. It has been established that pore-forming Yersinia proteins are protective antigens. The administration of them to laboratory animals induces the formation of species-specific immunity, which allows us to recommend porin protein as a component of chemical and genetic engineering vaccines. Porins are promising for the development of ELISA test systems for the diagnosis of pseudotuberculosis and intestinal yersiniosis, as well as immunopathologies caused by Yersinia bacteria. Given the high degree of similarity of the primary structures of Yersinia porins, it can be assumed that protective preparations created on their basis will protect against infections caused by intestinal yersiniosis, pseudotuberculosis and plague pathogens.